Manipulation of Mitophagy by "All-in-One" nanosensitizer augments sonodynamic glioma therapy - Qu, Fei; Wang, Pan; Zhang, Kun; Shi, Yin; Li, Yixiang; Li, Chengren; Lu, Junhan; Liu, Quanhong; Wang, Xiaobing (Autophagy, 2020)
Limited penetration of chemotherapeutic drugs through the blood brain barrier (BBB), and the increased chemo-resistance of glioma cells due to macroautophagy/autophagy, result in high tumor recurrence and extremely limited survival of glioma patients. Ultrasound-targeted microbubble destruction (UTMD) is a technique of transient and reversible BBB disruption, which greatly facilitates intracerebral drug delivery. In addition, sonodynamic therapy (SDT) based on ultrasound stimulation and a sonosensitizer, can be a safe and noninvasive strategy for treating glioma. We innovatively designed a smart "all-in-one" nanosensitizer platform by incorporating the sonoactive chlorin e6 (Ce6) and an autophagy inhibitor-hydroxychloroquine (HCQ) into angiopep-2 peptide-modified liposomes (designated as ACHL), which integrates multiple diagnostic and therapeutic functions. ACHL selectively accumulated in the brain tumors during the optimal time-window of transient UTMD-mediated BBB opening. The nanosensitizer then responded to a second ultrasonic stimulation, and simultaneously unloaded HCQ and generated ROS in the glioma cells. The sonotherapy triggered apoptosis as well as MAPK/p38-PINK1-PRKN-dependent mitophagy, in which the antioxidant relieved the sonotoxicity and MAPK/p38 activation, while the inhibition of MAPK/p38 attenuated the progression toward mitophagy by compromising redistribution of PRKN. Moreover, HCQ blocking autophagosome degradation, augmented intracellular ROS production and resulted in an oxidative-damage regenerative loop. ACHL-SDT treatment using this construct significantly inhibited the xenograft-tumor growth and prolonged the survival time of tumor-bearing mice, exhibiting an improved therapeutic efficiency. All together, we demonstrated a precision sonotherapy with simultaneous apoptosis induction and mitophagy inhibition, which served as an intelligently strategic sense of working alongside, providing new insights into the theranostics of brain tumors. ACHL: Angiopep-2-modified liposomes loaded with Ce6 and hydroxychloroquine; ACL: Angiopep-2-modified liposomes loaded with Ce6; BBB: blood brain barrier; Ce6: chlorin e6; CHL: liposomes loaded with Ce6 and hydroxychloroquine; CL: liposomes loaded with Ce6; CNS: central nervous system; DDS: drug delivery system; EB: Evans blue; FUS: focused ultrasound; HCQ: hydroxychloroquine; LRP1: low density lipoprotein receptor-related protein 1; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MAPK: mitogen-activated protein kinase; MBs: microbubbles; MTG: MitoTracker Green; MTR: MitoTracker Red; MTT: 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide; PBS: phosphate-buffered saline; PDI: polydispersity index; PINK1: PTEN induced kinase 1; PRKN/parkin: parkin RBR E3 ubiquitin protein ligase; ROS: reactive oxygen species; SDT: sonodynamic therapy; SQSTM1: sequestome 1; TA: terephthalic acid; TEM: transmission electron microscopy; TUNEL: terminal deoxynucleotidyl transferase mediated dUTP nick-end labeling; US: ultrasound; UTMD: ultrasound-targeted microbubble destruction.